2011
DOI: 10.1136/aim.2010.003285
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acupuncture on Postmenopausal Symptoms and Reproductive Hormones: A Sham Controlled Clinical Trial

Abstract: Background Acupuncture is commonly used to treat menopausal symptoms and other gynaecological conditions. In this study, the authors aimed to investigate whether acupuncture has an effect on menopausal symptoms and to explore whether this effect is related to changes in hormone levels. Materials and methods A total of 53 postmenopausal women were alternately assigned into two treatment groups: acupuncture (n=27) and sham acupuncture (n=26). Menopausal symptoms were assessed using the Menopause Rating Scale (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…[6][7][8][9][10] Furthermore, considering that sleep disturbances are strongly associated with the levels of sex hormone levels, researchers have studied the response of sex hormones to acupuncture in women experiencing menopause-related symptoms and have published conflicting results. [11][12][13] However, the effect of acupuncture on menopause-related sleep disturbances and whether the effectiveness of acupuncture in managing menopause-related sleep disturbances is affected by acupuncture-induced changes in sex hormones levels remain unclear.…”
mentioning
confidence: 98%
“…[6][7][8][9][10] Furthermore, considering that sleep disturbances are strongly associated with the levels of sex hormone levels, researchers have studied the response of sex hormones to acupuncture in women experiencing menopause-related symptoms and have published conflicting results. [11][12][13] However, the effect of acupuncture on menopause-related sleep disturbances and whether the effectiveness of acupuncture in managing menopause-related sleep disturbances is affected by acupuncture-induced changes in sex hormones levels remain unclear.…”
mentioning
confidence: 98%
“…[54][55][56] However, studies on acupuncture and levels of estrogen, progesterone, and VEGF in animal and human studies have not shown consistent results. [57][58][59][60][61][62] The findings of this review must be interpreted in the context of the primary literature. There does not appear to be a consistent control group, and studies in this review used multiple comparisons, including no intervention, placebo acupuncture, and oral or topical supplements and medications.…”
Section: Discussionmentioning
confidence: 99%
“…However, as longterm estrogen replacement therapy is associated with harmful systemic effects, safe and effective alternatives focused on the skin, such as topical estrogens and phytoestrogens, and tissue-specific drugs such as SERMs are preferred [71][72][73]. (11) Acupuncture was reported by some authors to be effective in reducing menopausal complaints such as sleep disturbances and hot flushes and in improving quality of life [74][75][76]. (12) Nastri et al…”
Section: Medical Measuresmentioning
confidence: 99%